Comparing the efficacy (RCT) of learning a dance choreography and practicing creative dance on improving executive functions and motor competence in 6–7 years old children. (March 2021) - Rudd, James; Buszard, Tim; Spittle, Sharna; O'Callaghan, Laura; Oppici, Luca
Abstract: Objectives: This study examined the effect of two different dance curriculums on executive functions and motor competence in 6–7 years old primary-school children across an 8-week period. One dance curriculum was underscored by creativity and the other was based on a choreographed dancing curriculum with high cognitive challenge. Design: Randomised-controlled trial. Methods: Sixty-two primary-school children (6.6 ± 0.5 years old; 47% females) participated for a control period in the regular school PE lessons, after which they were randomly assigned to two experimental groups – choreography dance group or creative dance group. The two experimental groups practiced dance for 8 weeks, twice a week, learning either a choreographed dance sequence with high cognitive challenge or creating their own dance sequence in a creative dance curriculum. Executive functions (working memory capacity, inhibition, and flexibility) and motor competence were assessed at three time points – baseline, pre-intervention and post-intervention. Results: There was a time effect for inhibitory control (p < 0.01), with a high improvement during the intervention (d = 0.76) than baseline (d = 0.46); for working memory capacity (p < 0.01), with a higher improvement during intervention (d = 0.43) than baseline (d = 0.31) in the high challenging task; and for motor competence (p < 0.01), with a higher improvement during baseline (d = 1.7) than intervention (d = 0.75); no other significant effects. Group differences revealed weak evidence that the choreography group improved inhibitory control and working memory more than the creative dance group. However, a check for pedagogy fidelity revealed that the creative-dance curriculum was not adopted as planned (i.e., high volume of teacher's instruction and small use of music). Conclusions: An 8-week dance intervention improved inhibitory control and potentially working memory capacity in grade one and two primary-school children. Contrary to prediction, the dance intervention did not improve motor competence beyond typical development. Discrepancy between the planned and adopted creative-dance curriculum suggests caution in interpreting results. This study provides new insights into the exercise-cognition relationship. Highlights: Two groups of children either learned a choreographed dance or created their own dance sequence for 8 weeks during PE classes. Both dance groups promoted development of inhibitory control, and there were sign of improvement for working memory capacity. In both groups, motor competence did not improve beyond typical development and cognitive flexibility did not improve at all. No between-group difference, but weak evidence in favor of the choreographed group for inhibitory control and working memory. Issues in the delivery of creative curriculum likely influenced results, which should be interpreted with caution.